Flexible oneanchor retaining building models calculation results comparing with experimental data - Grishin Anёdriy; Siplivets, Olaksandr (Academic journal Industrial Machine Building Civil Engineering, 2019)
Based on the previously described mathematical model implemented in software complex PLASTICA, nonlinear calculation of one anchor sheet pile wall together with surrounding soil medium has been performed. To assess the results reliability with experimental data tests Lazebnik G.E., calculations in PLAXIS 2D and classic Coulomb method are compared. The basis of a mathematical model incorporated the theory of plastic flow with hardening, which is based on the principle of maximum Mises. In general, it can be assumed that the calculations results in the software package PLASTICA using the proposed nonlinear models showed satisfactory agreement as compared with the experimental data